ISLAMIC GUIDANCE COUNSELING AS THE SOLUTION OF EDUCATION PROBLEMS FOR PEOPLE WITH DISABILITIES - Imam Rohani (Taqorrub: Jurnal Bimbingan Konseling dan Dakwah, 2023)
The purpose of this study is to describe Islamic counseling guidance techniques in dealing with learning difficulties for people with disabilities. This research used a qualitative approach to the type of library research by analyzing the related literature sources concerning the main and formulated research problems and also choosing the relevant reading sources in the field of study. People with disabilities has their own limitations, physically as well as mentally, intellectually, and sensory. They has rights to interact with other without any discrimination. Disability is not an obstacle, rather it is a different condition experienced by someone. To fulfil the rights of people with disabilities, there needs an inclusion school. In terms of education, not only people with disabilities who experience problem in learning but also normal people are facing problems in the process of learning. As the solution to tackle the learning problem is to hold Islamic counseling guidance, including starting with diagnosis, technically it can be done directly or indirectly. It can also be done in some Islamic guidance counseling services by creating a healthy learning atmosphere, provide learning motivation, direct guidance counseling service, giving advice, services through cooperation with other parties, group and individual guidance method.